Comprehensive Interpretation of Leadership from the Narratives in Literature - Kaushal, Nidhi; Mishra, Sanjit (Journal of Entrepreneurship, Business and Economics, 2017)
Narrative writings in literature are ample source of knowledge and are most easily understandable. In every old tradition, we find that people learn ethics and morality through oral forms of literature including short stories, ballads, and various other types of the genre. These narratives used to have tremendous influence on the listeners and readers seeking lessons in leadership. India, just like any other traditional country, has been rich in such genres whose practitioners effectively transmitted the required knowledge or the motivation to the learners in particular and the masses in general. The objective of this paper is to analyse and discus the art and craft of such stories which were useful in communicating the ideals of leadership. We assume that while leadership lessons can be learned from the study of literary writings, they can also be a valuable resource material for innovative learning the management skills. The role of the leader can be familiarly communicated in the form of the tales. Describing a positive psychological narrative from the text is the best way to manifesting an idea in to the minds of people. Research paper Keywords: Leadership, Literature, Management, Psychology Reference to this paper should be made as follows: Kaushal, N., Mishra, S. (2017). Comprehensive Interpretation of Leadership from the Narratives in Literature, Journal of Entrepreneurship, Business and Economics , 5 (2), 64–86.